Assessment of prediction and efficiency parameters for cryogenic no-vent fill. (July 2021) - Clark, Justin; Hartwig, Jason
Highlights: We present a simple parameter based on thermodynamics that can predict whether or not a non-vented fill will fail. The parameter is validated against 158 historical cases. The parameter has a 100% success rate. The parameter can be used for early-stage design and sizing of cryogenic non-vented transfer systems. Abstract: Future long-duration crewed and robotic missions will require efficient methods with which to transfer cryogenic propellant from a depot storage tank to a customer receiver tank in the microgravity of space. Because unsettled cryogenic liquid cannot be transferred in microgravity with the vent valve open, the receiver tank must be pre-chilled to some "target temperature" that is sufficiently cold to then allow a non-vented fill (NVF). Predicting this target temperature is difficult, however, but can be done. A predictive parameter based on 1st Law from Kim et al. [13] is extended to include parasitic heat leak as well as initial fill levels to permit an assessment across the consolidated NVF and no-vent top off database. An efficiency parameter is also proposed to determine efficiency of a given injection method/tank pair. The prediction parameter is applied to 158 historical tests over a wide range of fluids, injection methods, and tank geometries. Additionally, a parametric study is conducted to determine the influential factors that affect NVF. Results indicate a 100% success rate that the parameter can predict the failure of a non-vented transfer for a given initial state and desired final state.